Interactive augmented reality application development - "OnSnap! iOS application" - Weng, Grace Chanel Yi-Chian (2018)
Augmented Reality (AR) is the art of superimposing digital visuals over the view of the real-world. The technology has come a long way since it was first conceptualised. In the 21st Century, more people could access the power of AR through their hand-held devices, creating many opportunities for various industries including entertainment, commercial and engineering. Being imagery focused, AR can be a powerful tool in the advertising and commercial space. This project aims to design and develop “OhSnap!”, an augmented reality photo booth. The typical props used in traditional photo booth will be replaced with Two-dimensional (2D) and Three-dimensional (3D) virtual overlays. Furthermore, the implementation of sharing functionality allows users to send their photos to their email, share via social media platforms, or have their photos printed. An aesthetic responsive web application was also created to serve as an informational means to share more about OhSnap! AR photo booth with the public. The agile software development lifecycle was adopted to ensure that development process of the application would be successful. Firstly, the requirement analysis and design for the iOS application and website were identified. This is followed by the implementation and development phase. Lastly, the OhSnap! photo booth application was demonstrated in six different events.